The adoption and termination of profit sharing for employees: Does management's attitude play a role? - Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2016)
Examinations on the determinants of profit sharing usually focus on objective firm characteristics. Using data from manufacturing firms in Germany, this study shows that managers' subjective attitudes towards profit sharing also play an important role in the adoption and termination of this payment scheme. Positive management attitudes are associated with an increased likelihood of adopting profit sharing. While to some extent this entails failed experimentation, positive managerial attitudes also substantially contribute to a sustained use of profit sharing. The pattern of results holds even when controlling for a variety of objective firm characteristics.
Keywords: J33; M52; 330; profit sharing; management attitude; management discretion; subjective factors; experimentation